Teacher Attrition in The Bahamas: Survey of Teachers Leaving the Public School System, 1979-1981 - Stubbs, Salomi; Young, Jonathan (International Journal of Bahamian Studies, 2008)
As The Bahamas strives to Bahamianize its teaching force, the numbers of teachers leaving the work force is of concern. This study presents characteristics of Bahamian teachers resigning from employment with the Ministry of Education between the years 1979 and 1981.